(untitled) (American Journal of Interdisciplinary Research and Innovation, 2023)
Small-scale construction companies are predominant in developing countries and it is the most hazardous places in construction sites. Accidents mostly occur on construction sites due to a high level of safety ignorance and the nonchalant attitude of workers and management. The research aimed to investigate the actual behavior of workers at the selected sites regarding safety compliance, nutrition, alcohol use and smoking. This is highly necessary due to the high level of reported accidents and fatalities of the workers. And also recommend measures for improving how safety practices are implemented at a construction site. The interview and questionnaire approach was adopted to study the 150 participants. The data were analysed through SPSS. Research shows that 85% of construction workers are non-compliant with safety regulations because of their ignorance, poor safety training and lack of inspectors It was discovered that the majority of the small-scale contractors had no written health and safety policy within their companies and that made the level of understanding of the workers on safety and health policies very low. This has made the workers not care about wearing safety devices. The study was also extended to include behaviors related to food, alcohol and smoking. It was discovered that most of the workers don’t observe simple hygiene and eat junk meals at the site. They smoke and share cigarettes on the site, not knowing that it was a means of sharing communicable diseases.